Renewable energies and the policy mix: An analysis of renewable energy support strategies from a policy diffusion perspective - Luis Enrique Gutierrez Tavarez (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2013)
Renewable energy technologies (RET) have come to the fore in recent decades as a sensible and rational alternative to ensure that energy requirements are met within the context of growing energy demand and resource conservation worldwide. The question of energy provision sits at the complex juncture between economics, politics and international relations. As such, the topic cannot be understood simply in economic terms; its study needs to incorporate insights from politics and policy making for a more comprehensive perspective. This paper focuses on providing a more holistic picture of the varying impacts of policy decisions on the introduction of renewable energy technologies across different countries. In order to identify patterns and trends in the adoption of policy measures, this study makes use of the concept of Policy Mix, as proposed by Rogge and Reichardt (2013) and several concepts from innovation theory and policy diffusion. The first section of this paper presents the three main components of the study: the IEA-IRENA Joint Database for Renewable Energy Technologies, as its main source of information; and the concepts of Policy Mix and Policy Innovation used to analyse renewable energy (RE) support policies. The second section discusses the relevance of policy as a driver for the widespread adoption of RE and outlines the link between the policies analysed and the frame provided by the policy mix. Section three is then dedicated to analysing the countries in terms of policy diffusion, building upon the concept of policy mix. Innovator countries are initially taken as reference case studies in order to analyse the different channels through which policy spreads. The fourth section assesses the ad-vantages and limitations of applying the policy frame and is followed by the last section, which outlines further paths of research. By the end of the study it is expected that by integrating the concepts of policy mix and innovation diffusion into the analysis of renewable energies, it will be possible to achieve a better understanding of the effect policy structure and the reasons for policy implementation have on the efficacy of support mechanisms.
Keywords: 330